Extreme ultraviolet and x-ray transition wavelengths in Rb XXIV *The authors, Indu Khatri and Arun Goyal, were supported by the U. G. C., India for their Junior Research Fellowship and Man Mohan by the U.G.C. for Basic Science Research Fellowship. (20th August 2015) - Khatri, Indu; Goyal, Arun; Aggarwal, Sunny; Singh, A. K.; Mohan, Man
Abstract: Energy levels, radiative rates, oscillator strengths and line strengths are reported for transitions among the lowest 97 levels of the (1s 2 2s 2 2p 6 ) 3s 2 3p 2, 3s 2 3p3d, 3s3p 3, 3p 4, 3s3p 2 3d, and 3s 2 3d 2 configurations of Rb XXIV. A multiconfiguration Dirac–Fock (MCDF) method is adopted for the calculations. Radiative rates, oscillator strengths, and line strengths are provided for all electric dipole (E1), magnetic dipole (M1), electric quadrupole (E2), and magnetic quadrupole (M2) transitions from the ground level to all 97 levels, although calculations are performed for a much larger number of levels. To achieve the accuracy of the data, comparisons are provided with similar data obtained from the Flexible Atomic Code (FAC) and also with the available theoretical and experimental results. Our energy levels are found to be accurate to better than 1.2%. Wavelengths calculated are found to lie in EUV (extreme ultraviolet) and x-ray regions. Additionally, lifetimes for all 97 levels are obtained for the first time.